THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND COMPENSATION ON PERFORMANCE - Mohammad Mahrum; Ismu Hadjar; Nancy Yusnita (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2021)
This research is motivated by several interviews with leadership of Mafazah Moderen Islamic Boarding School, several problems regarding the performance of teachers conveyed by the Head of the Islamic Boarding School as informants, including, there are still many teachers who are less disciplined with working hours that have been determined by the staffing department, sometimes in the schedule of admission. Work still late and when the time runs out, the teacher always waits for orders and lacks initiative in work, many teachers complain about the leadership of the head in paying attention to teachers personally, the ineffective use of the facilities provided to support work teachers, many complaints about the current compensation system and the reason for compentation are factors that reduced teacher performance. This study was conduated to determine the effect of transformational leadership and compentation on teacher performance at Mafazah Moderen Islamic Boarding School. The number samples use in this study were 140 respondents, using simple linear regression analysis and multiple linear regression. The result show that transformational leadership has an effect on performance, these result are in line with Alzoraki, Rahman and Mutholib (2020), Yeni and Wote (2019, Cahyanu (2018). The result show that compentation has an effect the performance of the results of this study in line with research from Wekesa and Nyaroo MA (2015), Nursakinah (2015), and Ekawati (2018). The result of the analysis show that transformational leadership and compentation have an effect on performance simultaneously. The reslt of this study are in linewith Rismawati and Saly (2018) wich state that transformational leadership and compensation have positive and significabt effect on performance